The courtship call of Bokermannohyla ibitiguara (Anura: Hylidae) and details of its mating behavior - Nali, Renato C. [UNESP]; Turin, Rubens A. F.; Prado, Cynthia P. A. [UNESP] (Inst Ciencias Naturales, Museo Historia Natural, 2022)
Complex courtships have been described for neotropical frogs, but detailed quantifications of calls emitted during this behavior are still rare. Herein, we describe the courtship call of Bokermannohyla ibitiguara, a gladiator tree frog from the Brazilian Cerrado, as well as the female behavior during courtship, and the clutch characteristics. Moreover, we statistically compare the acoustic parameters of the advertisement and courtship calls. We observed that the female also touches the male during courtship and that the courtship call is overall similar to the long note of the advertisement call. However, we uncovered significant differences in frequencies and pulses between these two call types emitted by the same male. This ability to modify call parameters is consistent with previous results in aggressive contexts and reinforces sexual selection as a strong mechanism shaping call variation in this species. This is the third courtship call described for the genus and we emphasize that the description of rare behaviors, even in artificial conditions, is important to advance the field of behavioral ecology across taxa.
Keywords: Amphibians; Bioacoustics; Cophomantini; Sexual selection; Tactile stimuli